325 Dealing with cardiac amyloidosis diagnosis: keep calm and use the magnifying glasses!. (8th December 2021) - De Michieli, Laura; Licchelli, Luca; Sinigiani, Giulio; Berno, Tamara; Barbera, Mila Della; Rizzo, Stefania; Basso, Cristina; Marra, Martina Perazzolo; Iliceto, Sabino; Cipriani, Alberto
Abstract: Methods and results: Case report— male, 71 years old. Past medical history—arterial hypertension, dyslipidemia, tobacco abuse. COPD on nocturnal CPAP therapy. Rheumatic polymyalgia on steroid therapy. Previous unprovoked deep vein thrombosis on anticoagulation with rivaroxaban. Bilateral carpal tunnel surgeries 8 years ago. Spontaneous left biceps tendon rupture 4 year ago. IgA kappa monoclonal gammopathy of undetermined significance (MGUS). Mild interventricular septum (IVS) hypertrophy on echocardiography since 2018. In 2019 IVS was 18 mm with granular sparkling appearance. In February 2020 he was hospitalized for initial heart failure and COPD exacerbation. In 2021 he developed worsening dyspnoea. He underwent cardiological evaluation in a spoke hospital and a cardiac magnetic resonance (CMR) suggested infiltrative cardiomyopathy. Bone scintigraphy showed moderate cardiac uptake (Perugini Score 2). Following haematological evaluation, fat pad biopsy was performed, and amyloid was detected on Congo red staining. Classification of the amyloid fibril protein was not performed. Bone marrow biopsy, even though of suboptimal quality, was negative for amyloid and for plasma cellular infiltration. Bone marrow aspirate showed 11% of plasma cells and multiple myeloma was therefore hypothesized. Recent medical history—he was evaluated in our Cardiac Amyloid Outpatient Clinic in May 2021. He was symptomatic for dyspnoea (NYHA class III) and exercise intolerance, diffuse osteo-muscolar pain, and extremities paresthesia. His blood pressure was on the low side of normality with necessity of anti-hypertensive therapy downgrading. Signs and symptoms of hematological disease were not present. We required to analyse the fat pad specimen in order to perform amyloid fibril protein typing; with immunoelectron microscopy, transthyretin (TTR) was identified as the amyloid fibrils precursor (no light chains could be identified). We considered performing endomyocardial biopsy to exclude the coexistence of ATTR amyloidosis and light chains (AL) amyloidosis in the heart but, given the history, clinical picture, and fat pad biopsy results, we felt that cardiac ATTR was the most probable diagnosis and we decided to proceed with a close cardiological and haematological follow-up. TTR genetic testing is ongoing. Conclusions:  ATTR cardiac amyloidosis is an emerging cause of heart failure, especially with preserved ejection fraction, in the older population. However, these patients frequently present with dysproteinemias and bone marrow abnormalities, up to multiple myeloma, raising the issue of differential diagnosis between ATTR and AL amyloidosis. According to the latest European Consensus Document, in the presence of cardiac uptake at bone scintigraphy (Grades 1–3) and positive haematologic tests, histological confirmation (usually cardiac) is necessary to subtype amyloid infiltration. In our case, the patient had positive Congo Red-stained fat pad biopsy, but the typing of the amyloid deposition was not performed. After referral to a Center with a Cardiac Amyloid Outpatient Clinic with a specialized Pathology Unit, we could further proceed with diagnostic workup and identify the amyloid deposition as ATTR; of note, fat pad biopsy is positive in just 15–25% of ATTR amyloidosis. Moreover, close collaboration with Hematology was necessary to assess the risk of AL amyloidosis and to provide a close and targeted follow-up. Endomyocardial biopsy was not performed after consideration of the various elements suggestive for ATTR cardiac amyloidosis, but the patient will be evaluated periodically and closely to potentially reassess this decision.